ADVENTURE SHOPPING, IDEA SHOPPING, VALUE SHOPPING DAN SOCIAL SHOPPING TERHADAP IMPULSE BUYING TENDENCY - Suryanto, Irine (Arthavidya Jurnal Ilmiah Ekonomi, 2024)
Abstrak Penelitian ini meneliti pengaruh adventure shopping, idea shopping, value shopping dan social shopping terhadap impulse buying tendency. Pendekatan metode kuantitatif digunakan dalam peneltian ini dengan menggunakan responden pada Tokopedia Online Shop. Ditemukan bahwa adventure shopping dan value shopping terhadap impulse buying tendency kosumen Tokopedia online shop di Surabaya. Sedangkan value shopping dan social shopping tidak berpengaruh terhadap impulse buying tendency kosumen Tokopedia online shop di Surabaya.Kata Kunci: Adventure Shopping, Idea Shopping, Value Shopping Dan Social Shopping Terhadap Impulse Buying TendencyAbstract The purpose of this study was to determine the effect of adventure shopping, idea shopping, value shopping and social shopping on impulse buying tendency. The approach used in this study is a quantitative method using respondents in the Tokopedia Online Shop. It was found that adventure shopping and value shopping to impulse buying tendencies of Tokopedia online shop consumers in Surabaya. While value shopping and social shopping do not affect the impulse buying of the Tokopedia online shop consumer tendency in Surabaya.Keywords: Adventure Shopping, Idea Shopping, Value Shopping and Social Shopping Against Impulse Buying Tendency